Redesign Sistem Pengering Pada Mesin Freezer Multifungsi Dengan Memanfaatkan Panas Dari Kondensor - Yogi Sandi Pratama; Projek Priyonggo; George Endri Kusuma (Politeknik Perkapalan Negeri Surabaya, 2023)
In previous studies, a Multifunction Freezer machine was made, which is a tool similar to a refrigerator in general, namely to cool food ingredients, but the advantages of this Multifunction Freezer Machine are made so that it can have 2 uses, namely, to cool and dry food ingredients such as fish etc. The weakness of the drying system in the previous multifunctional freezer machine was in the wrong placement of the fan and condenser which resulted in a less than optimal reduction of the water content in the ingredients (fish) for processing salted fish. The method used is to redesign or redesign the placement of the fan and condenser so that the drying system can work optimally and can reduce the water content of the ingredients (fish) as needed for salted fish processing. This research is to redesign the Multifunctional Freezer machine which was previously made by placing the fan and condenser on the left side of the drying chamber and by adding a glass heater after the condenser and the results obtained are room temperature 48.7 oC and fish temperature 34.2 oC, moisture content 6.583%, drying rate 0.378 gram/minute and performance factor 3.74 within 180 minutes or 3 working hours of a Multifunctional Freezer Machine.